1961
DOI: 10.1119/1.1986484
|View full text |Cite
|
Sign up to set email alerts
|

Emission of Radio-Frequency Waves from Plasmas

Abstract: Observations of the radio-frequency emission from extraterrestrial plasmas and plasmas produced in the laboratory are described, and various attempts at interpretation of the results are reviewed. Estimates are made of the probable loss of radiant energy from plasmas in proposed thermonuclear reactors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1963
1963
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…To determine whether this plasma is strongly ionized, the electron density can be estimated using the requirements for opacity [1,2,23,24]. The absolute spectral intensity I λ at wavelength λ can be calculated using [25],…”
Section: Cooling Phase (T > 25 Ns) -Lasting 100s Of Nanoseconds Thismentioning
confidence: 99%
“…To determine whether this plasma is strongly ionized, the electron density can be estimated using the requirements for opacity [1,2,23,24]. The absolute spectral intensity I λ at wavelength λ can be calculated using [25],…”
Section: Cooling Phase (T > 25 Ns) -Lasting 100s Of Nanoseconds Thismentioning
confidence: 99%
“…Unfortunately, as was shown later, Twiss had not included the statistical weights of the electrons correctly. A correct calculation (8) showed that under the circumstances described by Twiss, negative absorption is not possible. The conditions necessary for negative ab-sorption have been reviewed in a very lucid fashion by Wild et al (9).…”
mentioning
confidence: 99%
“…so that the phase velocity of light is greater than c. vv is the plasma frequency: V ( ne) (8) where ne is the number density of thermal electrons. Roughly speaking, the result of this change of phase velocity is that the Lorentz factor y in Eq.…”
mentioning
confidence: 99%
“…Later, Rai et al [1972] based on the previous reference of Bekefi and Brown [1961], found that the bremsstrahlung process is a possible source of RF emissions in UHF and microwaves measured during some lightning processes. The authors demonstrated how the full ionized plasma in the return stroke does not radiate microwave power since its absorption coefficient lets to an optical thickness much greater than the unity.…”
Section: Bekefi and Brownmentioning
confidence: 99%